Transplantation of human autologous synovial mesenchymal stem cells with trisomy 7 into the knee joint and 5 years of follow‐up. (3rd August 2021) - Mizuno, Mitsuru; Endo, Kentaro; Katano, Hisako; Amano, Naoki; Nomura, Masaki; Hasegawa, Yoshinori; Ozeki, Nobutake; Koga, Hideyuki; Takasu, Naoko; Ohara, Osamu; Morio, Tomohiro; Sekiya, Ichiro
Abstract: Mesenchymal stem cells (MSCs) can show trisomy 7; however, the safety of these cells has not been fully investigated. The purposes of this study were to determine the ratio of patients whose synovial MSCs were transplanted clinically, to intensively investigate MSCs with trisomy 7 from a safety perspective, and to follow up the patients for 5 years after transplantation. Synovial MSCs at passage 0 were transplanted into a knee for degenerative meniscus tears in 10 patients, and the patients were checked at 5 years. The synovial MSCs were evaluated at passages 0 to 15 by G‐bands and digital karyotyping, and trisomy 7 was found in 3 of 10 patients. In those three patients, 5% to 10% of the synovial MSCs showed trisomy 7. The mRNA expressions of representative oncogenes and genes on chromosome 7 did not differ between MSCs with and without trisomy 7. Whole‐genome sequencing and DNA methylation analysis showed similar results for MSCs with and without trisomy 7. Transplantation of human synovial MSCs with trisomy 7 into eight mouse knees did not result in tumor formation under the skin or in the knees after 8 weeks in any mouse, whereas transplanted HT1080 cells formed tumors. In vitro chondrogenic potentials were similar between MSCs with and without trisomy 7. Five‐year follow‐ups revealed no serious adverse events in all 10 human patients, including 3 who had received MSCs with trisomy 7. Overall, our findings indicated that synovial MSCs with trisomy 7 were comparable with MSCs without trisomy 7 from a safety perspective. Abstract : Trisomy 7 is often found in synovial mesenchymal stem cells (MSCs). However, the safety of these cells after transplantation has not been investigated. The authors found no serious adverse events, including tumor formation, in any of our 10 patients at 5 years after transplantation of MSCs with or without trisomy 7.